Morphological diversity of the metathoracic spiracle in the Lygaeoidea (Hemiptera: Heteroptera). (October 2020) - Zhang, Yan; Kment, Petr; Cai, Bo; Gao, Cui-Qing; Shi, Xue-Qin; Liu, Hua-Xi; Ye, Zhen; Bu, Wen-Jun
Abstract: Spiracles are the openings in the exoskeleton of insects through which air enters into the respiratory system that is formed by a series of tubes called tracheae. They are primarily located on the abdomen, but can also occur on the thorax, including the metathorax. An insect metathoracic spiracle is usually composed of an external opening and a more internal filter apparatus. We propose new terminology for these structures, and we explore the value in their use in taxonomic and phylogenetic studies within the true bug infraorder Pentatomomorpha, with emphasis on the superfamily Lygaeoidea (Insecta: Hemiptera: Heteroptera). These structures were studied using scanning electron microscopy. Two types of metathoracic spiracle external openings were recognized: a narrow opening (type N), which is slit-like; and a wide opening (type W), with internal fine structures located between the mesothoracic and metathoracic margins of the interpleural suture clearly visible. The filter apparatus in the Pentatomomorpha consists of modified mushroom bodies of the metathoracic scent gland evaporatorium, for which the term mycoid filter processes is proposed. Eight different types of mycoid filter processes, and an unmodified microsculpture type (a type with usual cuticular microsculpture) and filter setae can be found on the anterior or posterior margins of the metathoracic spiracle. We believe the wide opening (type W) to be the plesiomorphic character state in the Pentatomomorpha, with multiple, independent transformations leading to the narrow opening in Lygaeoidea. Considerable variability in the structure of the spiracle opening (in Lygaeoidea), and in the structure of the mycoid filter processes (in Pentatomomorpha) was detected. Overall, we found the morphology of these structures to be of limited value concerning the taxonomy or for determining phylogenetic relationships of the higher taxa (families) of Pentatomomorpha, but they may be useful as additional evidence for taxonomic and phylogenetic studies at the generic and perhaps the tribal levels.